Rancang Bangun Game Getuk Shooter Menggunakan Algoritma Collision Detection Berbasis Android - Fauziah Fauziah; Eka Mutia Putri (Universitas Kuningan, 2021)
Android Based Game has grown rapidly, with the growing user of smartphones and tables in this world. The game maker industry also has many opportunities to produce games. Many advantages of producing games because of many enthusiasts for the game. Making game is an interesting field to learn because of the great potential both in terms of science and in terms of commercial. In this study the author designs and builds an application of the Android based Getuk Shooter game using Collision Detection algorithm for collision attack detection. The method used in this research is RUP method, which is method of software development done repeatedly. The result of this research is to produce Android based mobile game in the form of single player getuk vertical shot that can train the dexterity of player with 2D display and it consists of 3 levels, which can run on android smartphone.Key words : Android, game, collision, shooting